Calvyn oor die verskynsel van demonologie - C. F. C. Coetzee (Acta Theologica)
Scripture teaches an increased occurrence of demonology at the end of time (cf. 1 Tim. 4:1; Rev. 16:13, 14). This truth can already be observed in increasing occultism, witchcraft and other forms of demonology in Europe and in Africa, where traditional African culture plays a decisive role. In order to combat demonology from a Reformed point of view, it is important to note John Calvin’s opinion and approach. Not only was he one of the greatest Reformed theologians, but he also lived and worked in the “devil’s golden age”. Calvin’s hermeneutical principles and his interpretation of Scripture are still essentially important.